Selection of the MOORA Method in Motorcycle Lending Decisions - Khairunnisa Khairunnisa; Madikatul Sania; Rohan Kristini Purba; Mesran Mesran (The IJICS (International Journal of Informatics and Computer Science), 2023)
Nowadays, many people need vehicles for their daily activities, so motorcycle loans are an alternative. Motorcycle credit is a credit facility that aims to finance the purchase of motorcycles. In granting motorcycle credit, a system is needed that is able to select customers who are entitled to receive their applications according to predetermined criteria. This study uses a decision support system (DSS) as a problem solver in decision making. A decision support system (DSS) is a system that can provide the ability to solve problems in semi-structured and unstructured situations. One of the DSS methods used to solve decision-making problems This decision is the MOORA method. The MOORA method is a method whose calculations are made as simple as possible